Facet-sparing lumbar decompression with a minimally invasive flexible MicroBlade Shaver® versus traditional decompression: quantitative radiographic assessment - Lauryssen C; Berven S; Mimran R; Summa C; Sheinberg M; Miller LE; Block JE (Clinical Interventions in Aging, 2012)
Carl Lauryssen,1 Sigurd Berven,2 Ronnie Mimran,3 Christopher Summa,4 Michael Sheinberg,5 Larry E Miller,6,7 Jon E Block71Tower Orthopedics, Beverly Hills, CA, USA; 2Department of Orthopedics, University of California, San Francisco, San Francisco, CA, USA; 3Pacific Brain and Spine, Castro Valley, CA, USA; 4The Spine Clinic of Monterey Bay, Soquel, CA, USA; 5Danville, CA, USA; 6Miller Scientific Consulting Inc, Arden, NC, USA; 7The Jon Block Group, San Francisco, CA, USABackground: Laminectomy/laminotomy and foraminotomy are well established surgical techniques for treatment of symptomatic lumbar spinal stenosis. However, these procedures have significant limitations, including limited access to lateral and foraminal compression and postoperative instability. The purpose of this cadaver study was to compare bone, ligament, and soft tissue morphology following lumbar decompression using a minimally invasive MicroBlade Shaver® instrument versus hemilaminotomy with foraminotomy (HL).Methods: The iO-Flex® system utilizes a flexible over-the-wire MicroBlade Shaver instrument designed for facet-sparing, minimally invasive “inside-out” decompression of the lumbar spine. Unilateral decompression was performed at 36 levels in nine human cadaver specimens, six with age-appropriate degenerative changes and three with radiographically confirmed multilevel stenosis. The iO-Flex system was utilized on alternating sides from L2/3 to L5/S1, and HL was performed on the opposite side at each level by the same investigator. Spinal canal, facet joint, lateral recess, and foraminal morphology were assessed using computed tomography.Results: Similar increases in soft tissue canal area and decreases in ligamentum flavum area were noted in nondiseased specimens, although HL required removal of 83% more laminar area (P < 0.01) and 95% more bone resection, including the pars interarticularis and facet joints (P < 0.001), compared with the iO-Flex system. Similar increases in lateral recess diameter were noted in nondiseased specimens using each procedure. In stenotic specimens, the increase in lateral recess diameter was significantly (P = 0.02) greater following use of the iO-Flex system (43%) versus HL (7%). The iO-Flex system resulted in greater facet joint preservation in nondiseased and stenotic specimens. In stenotic specimens, the iO-Flex system resulted in a significantly greater increase in foraminal width compared with HL (24% versus 4%, P = 0.01), with facet joint preservation.Conclusion: The iO-Flex system resulted in significantly better decompression of the lateral recess and foraminal areas compared with HL, while preserving posterior spinal elements, including the facet joint.Keywords: decompression, laminectomy, lumbar, minimally invasive, stenosis, MicroBlade Shaver, iO-Flex system